Human parvovirus B19 associated dilated cardiomyopathy. (5th August 2013) - Jain, Parul; Jain, Amita; Khan, Danish Nasar; Kumar, Mala
Abstract : We describe two children presenting with acute left ventricular dysfunction. Both cases had evidence of dilated cardiomyopathy, requiring inotropic support and were tested for cardiotropic viruses by conventional or real-time polymerase chain reaction using specific primers for enteroviruses, human parvovirus B19, Adenoviruses, Epstein-Barr virus (EBV), herpes simplex viruses 1 and 2 (HSV), human herpes virus-6 (HHV-6) and cytomegalovirus (CMV). IgG and IgM antibodies against parvovirus B19, EBV, HSV and CMV were also tested by ELISA. One case tested positive for parvovirus B19 infection and recovered completely within 6 months in absence of any specific therapy. The other case tested positive for parvovirus B19 infection in association with hypocalcaemia and was cured following standard heart failure therapy along with calcium and vitamin D supplementation. Sequence analysis of DNA products from both patients revealed genotype 3. To best of our knowledge this is first report of circulating genotype 3 from India.